Strategi Penguatan Sintesa Partisipasi Masyarakat dan Manajemen Perencanaan Pembangunan Daerah di Kabupaten Blora - Muayyadah, Nailatul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
The implementation of the musrenbang is a formal means of community participation even though it has met normative rules but has not been optimal in its participation. This study aims to describe how the Blora community participates in the making of the RKPD based on the categories of urban, rural, and samin communities and how the efforts to synthesize the culture of participation and management of RKPD making. This study applies a qualitative approach . The results of this study prove there are differences in the culture of participation between urban, rural and samin communities. A number of factors that support community participation include legislation; the existence of SIPPD; and the enthusiasm of the local government and the community to advance their region. A number of inhibiting factors still occur including the low capacity of the community; domination of local elites; the absence of a verification and guarantee mechanism for the proposed results of the musrenbang; and the uneven capacity of planners on every line of planning.